Reading Abilities in Native Lithuanian Language of 11th Grade Students - Ancevičiūtė, Ieva; Vilkienė, Loreta (Pedagogika, 2023)
The objective of the research was to find out whether the specific reading abilities (to understand the essence of a text, to understand important details, to interpret, to find arguments, to draw conclusions) of Lithuanian eleventh-grade students are equally well developed and whether different abilities manifest equally irrespective of the type of the text. The paper also sought to provide insights as to which sociolinguistic factors have a significant impact on the reading skills of the students. The research material consists of answers of 120 students to the sociolinguistic questionnaire as well as performance results of the reading skills test, which have been analysed using the methods of descriptive statistics and conclusion statistics. The regression analysis has also been carried out. Analysis of the results revealed that the students have best developed the ability to understand important details and find arguments, and most of all they lack ability to properly interpret the thoughts of the text and draw conclusions. In terms of all abilities, a descriptive text was the easiest for the students, and a narrative text was seen by the students as the most complex. Statistically the results of the students from small towns did not differ significantly from the results of Vilnius students (p = 0,247). Statistically, the overall reading test results of the male students are significantly lower than those of the female students (p < 0,01). Sometimes (p < 0,01), often and always (p < 0,01) reading fiction books for pleasure has a statistically significant effect in general on the reading skills of the students.